Magic assistants in the Kalmyk and Tuvan epics - Ubushieva, Danara V. (The New Research of Tuva, 2019)
The article analyzes archaic roots of the Kalmyk epic of Jangar traced in the Song of Khara Kines (included in the latter) and the Tuvan legend of Khunan Kara. The paper examines the category of magic assistants – miraculous skills of the epic characters and ones in the forms of humans, animals and other helpful characters. The comparative analysis of the Song of Khara Kines included in the early Baga Tsokhor Cycle of the Kalmyka epic and the Tuvan legend of Khunan-Kara concludes the former is actually based on nuclear archaic elements of preceding epic systems. The epic sets forth personified skills of its characters rather than those of magic assistants. The epic characters can turn into lousy boys and possess magic attributes, which mirrors the archaic initiation rituals.